TRIPLE ACTION PALATE EXPANDER - Svetlana Yordanova; Miroslava Yordanova; Stoyan Yovchev (Peytchinski Publishing, 2011)
Malocclusion correction essentially involves expansion of the maxilla, protrusion of anterior teeth and opening the bite. Expansion is often the stage preceding the treatment with fixed appliances. The elevation of the occlusion using accomplished with different devices (bite planes -fixed or removable, composite material on the occlusall surface of molars) carries the risk of breaking or debonding them.The present article proposes an expanding appliance with triple action as a therapeutic means of choice in an orthodontic treatment with fixed appliances. The expander can simultaneously be used to protrude upper teeth, to expand the upper jaw and disarticulate the occlusion. It can be easily fabricated in clinical conditions, causes no discomfort and does not hamper oral hygiene because it can be removed and cleaned.